The Genome-Wide EMS Mutagenesis Bias Correlates With Sequence Context and Chromatin Structure in Rice - Yan, Wei; Deng, Xing Wang; Yang, Chengwei; Tang, Xiaoyan (Frontiers in Plant Science, 2021)
Ethyl methanesulfonate (EMS) is a chemical mutagen believed to mainly induce G/C to A/T transitions randomly in plant genomes. However, mutant screening for phenotypes often gets multiple alleles for one gene but no mutant for other genes. We investigated the potential EMS mutagenesis bias and the possible correlations with sequence context and chromatin structure, using the whole genome resequencing data collected from 52 rice EMS mutants. We defined the EMS-induced single nucleotide polymorphic sites (SNPs) and explored the genomic factors associated with EMS mutagenesis bias. Compared with natural SNPs presented in the Rice3K project, EMS showed a preference on G/C sites with flanking sequences also higher in GC contents. The compositions of local dinucleotides and trinucleotides were also associated with the efficiency of EMS mutagenesis. The biased distribution of EMS-induced SNPs was positively correlated with CpG numbers, transposable element contents, and repressive epigenetic markers, but negatively with gene expression, the euchromatin marker DNase I hypersensitive sites, and active epigenetic markers, suggesting that sequence context and chromatin structure might correlate with the efficiency of EMS mutagenesis and DNA repair. Exploring the genome-wide features of EMS mutagenesis and correlations with epigenetic modifications will help the understanding of DNA repair mechanism.